Pengembangan Sistem Berbasis Web untuk Monitoring LEAD (Studi Kasus Website Document Solution) - Mochammad Dearifaldi Al Ikhsan; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Online marketing or often called digital marketing is marketing with the concept of promoting a product or service through internet-based media, one of which is a website. The existence of a website raises new problem, namely the difficulty in recognizing website visitors. The use of website to improve marketing strategies needs to be done by recognizing website visitors which will be the lead for a company. Without recognizing the website visitors, the salesperson cannot determine the customer to be contacted. To overcome these problems, a system of monitoring leads is built on the website by applying the waterfall development model. The technology used in this research is the laravel framework which are implemented using the PHP and Javascript programming languages. This research produces a monitoring lead system that can monitor leads, recognize the behavior of website visitors, find out the recommendation of leads, and conduct lead management. In the calculation process, the recommendation of leads uses the weighted product method which is a decision support method that uses weighting, where alternative values and predetermined criteria are needed. This weighted product method is expected to provide recommendation of leads in the form of rating so the salesperson know which leads should be followed up. Testing is done by using the white-box and blackbox methods which show the results that the system functions are in accordance with the main functional specifications, which is displaying various lead information. Usability testing produces a value of 91.67 which indicates that the system has made it easy for users.